Continuing Education Programs and Student Participation at the University of the Republic (Uruguay): An Analysis of Professional Clusters Based on Preferences - Escuder Rodríguez, Santiago (2025)
Continuing education and professional training are highly relevant phenomena in today's labor market. However, these processes are far from uniform. This study examines, at a national level (Uruguay), the characteristics of participants, the activities of the Continuing Education Program of the University of the Republic (PEP), and the relationships established among them. It also explores the profiles of students and their preferences for specific content and learning methods. The research draws on surveys conducted by the Central Unit of Continuing Education (UCEP) and data on activities and enrollments provided by all Continuing Education Units within the University. Analytical techniques used include word clouds based on course titles, Multiple Correspondence Analysis (MCA), and hierarchical classification using Ward's method (clusters) to identify student profiles. Clear preferences emerge based on academic disciplines and the geographical proximity of professionals to educational centers. Key findings include the permeability of knowledge in the course offerings in social sciences and the preference of professionals—particularly in the health sector—for courses focused on technical content and the acquisition of hard skills. There is also a notable inclination toward virtual training. 2.14.0.0